Case Report: Early detection of neonatal volvulus by ultrasound in a 2-day-old neonate: timely intervention prevents complications - Chen, Yunqin; Lu, Hongping; Yu, LinJun; Wang, Lizhen; Li, Jie; Liang, Fuen; Li, Haiting; Chen, Xiyang; Yuan, Junhui; Tao, Enfu (Frontiers in Pediatrics, 2025)
Intestinal malrotation is a congenital anomaly arising from improper rotation or fixation of the embryonic gut, potentially leading to life-threatening complications such as volvulus. It typically presents within the first month of life with symptoms including bilious vomiting and scaphoid abdomen. In this report, we describe a case involving a 2-day-old term neonate who exhibited two episodes of hematochezia and one episode of hematemesis, without accompanying scaphoid abdomen or bilious vomiting. Initial laboratory investigations revealed metabolic acidosis (lactate 4.6 mmol/L, base excess −7.28) and positive occult blood (+++). A bedside abdominal ultrasound identified a whirlpool sign, prompting immediate transfer to a tertiary care facility. An emergency laparotomy confirmed a 480 degrees clockwise volvulus without necrosis. The patient underwent a Ladd's procedure and appendectomy, resulting in full recovery. This case represents the earliest documented instance of malrotation presenting with hematochezia and hematemesis within the first 48 hours of life. The absence of necrosis despite gastrointestinal bleeding suggests that hemorrhage in cases of volvulus may precede irreversible ischemia, thereby underscoring the necessity for urgent ultrasound evaluation. We propose that hematochezia in neonates should prompt urgent ultrasound evaluation for malrotation, even in the absence of classic symptoms.